Design, synthesis and biological evaluation of Novel Curcumin Analogs with anticipated anticancer activity - Iten M. Fawzy; Khairia M. Youssef; Nasser S.M. Ismail; J. Gullbo; Khaled A.M. Abouzid (SpringerOpen, 2015)
Context: Extensive research conducted within past years revealed that curcumin is a highly pleiotropic molecule that interacts with a diverse range of molecular targets and hence it possess anti-proliferative activities against tumor cells.The great similarities between curcumin analogs and chalcones inspired their testing against tubulin enzyme activity as recent research revealed that chalcones possess cytotoxic activity associated with tubulin inhibition and interference with microtubule formation, which is essential in mitosis and cell replication. Objective: Novel Curcumin analogs were designed, synthesized and tested for their antitumor activities. Also in silico and in vitro studies has been performed to predict the binding affinity of the target compounds and to test their ability to inhibit tubulin assembly and act as microtubule destabilizing agents. Methods: Six novel curcumin analogs were designed & synthesized with 3,5-dibenzylidenepiperidin-4-one core moiety. Results: Compounds showed interaction energy comparable to or within the range of podophyllotoxin itself when docked into the colchicine binding site of tubulin using the podophyllotoxin-tubulin complex (PDB 1SA1). Conclusion: Compounds showed moderate anticancer activity and moderate ability to destabilize microtubules and thus inhibiting tubulin polymerization, as a result; these compounds could be used for further future development to obtain more potent analogs.